A new adaptive controller for volume-controlled mechanical ventilation in small animals. (1st May 2014) - Huhle, Robert; Spieth, Peter M.; Güldner, Andreas; Koch, Thea; Abreu, Marcelo Gama de
ABSTRACT Background: This study aimed to develop and evaluate an adaptive control system for volume-controlled ventilation (VCV) in small animals to guarantee accurate delivery of tidal volume (VT) in the presence of changes in lung mechanics. Methods: The adaptive control system to control the Harvard Inspira ventilator was designed and evaluated on a custom-made physical model during step changes of resistance and elastance of the respiratory system assessing difference in minute ventilation (ΔMVc) during convergence cycles (NC). The controller was then evaluated during conventional and variable volume VCV in rats with acute respiratory distress syndrome (ARDS) induced by intratracheal HCl (six animals/group), where the difference between desired and applied VT (dVT, d), its root-mean square error (RMSE) and relative deviation from target minute ventilation (ΔMV) were determined. Results: The controller showed fast convergence NC < 20 cycles with an acceptable ΔMVC < 10% in simulations and nearly abolished dVT, d (VCV: 0.23 ± 0.1 mL to 0.0 ± 0.0 mL, P < .001 and vVCV: 0.05 ± 0.8 mL to 0.0 ± 0.0 mL, P < .001), significantly reduced RMSE (VCV: 0.23 ± 0.1 to 0.04 ± 0.01 mL, P < .001 and vVCV: 0.13 ± 0.04 to 0.08 ± 0.02 mL, P < .001) and ΔMV (VCV: 11.6 ± 4.2 to 0.04 ± 0.15%, P < .001 and vVCV: −3 ± 3.8 to −0.35 ± 1.3 %, P < .001) in animal experiments. In VCV the improvement was more pronounced, due to reduced respiratory system elastance in this group (VCV: 5.6 cmH2O mL−1 versus vVCV: 3.8 cmH2O mL−1, P < .001). Conclusions: The new adaptive controller ensured accurate delivery of VT in VCV and proved valuable for mechanical ventilation of small animals especially in ARDS research.